Question #f837c

2 Answers
May 11, 2017

I tried this:

Explanation:

We can use the fact that:
sectheta=1/costheta
and
tantheta=(sintheta)/(costheta)

and write:

(1-costheta)(1+costheta)1/cancel(cos^2theta)=sin^2theta/cancel(cos^2theta)

multiply on the left to get:

1-cos^2theta=sin^2theta that it is true!

Remebering that:

sin^2theta+cos^2theta=1

May 15, 2017

(1 - cos theta)(1 + cos theta) sec^2 theta = (1 - cos^2 theta)* 1/cos^2 theta

note : sec^2 theta = 1/cos^2 theta and 1 -cos^2 theta = sin^2 theta

(1 - cos^2 theta)* 1/cos^2 theta= sin^2 theta/ cos^2 theta = tan^2 theta --> proved